Silenced Archive of the Holodomor: The Ukrainian Civil Committee for Saving Ukraine, Transnational Humanitarianism, and Networks of National Compassion - Koziura, Karolina (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2023)
It is a commonly held contention among scholars that the Great Ukrainian Famine of 1932–33—denied by the Soviet authorities while it was happening—received no relief in the form of organized international humanitarian aid. Thus, accounts of the famine rarely (if ever) feature a humanitarian narrative. By analyzing the activity of the Ukrainian Civil Committee for Saving Ukraine (Ukraїns'kyi Hromads'kyi Komitet Riatunku Ukraïny), this article challenges such views, as it situates interwar famine-related humanitarianism within the context of small-scale ethnic aid committees working in the interests of the starving across Europe. The records of the Ukrainian Committee stored at the National Library of Poland, as a group, constitute the “silenced archive of the Holodomor”—namely, scattered evidence of the famine that has been affected by displacement and erasure. Analyzing these largely understudied materials, this article argues that the official denial of the famine triggered the deployment of a transnational humanitarian narrative based on what the author calls “national compassion”—a moral duty and obligation uniting Ukrainians across borders. The article, moreover, points to the importance of situated knowledge, information networks, and documentation as tools in countering acts of violence and the power of repressive regimes.